Partial oxidation of methane over CaO decorated TiO2 nanocatalyst for syngas production in a fixed bed reactor - Khoja, Asif Hussain; Javed, Ahad Hussain; Naqvi, Salman Raza; Shakir, Sehar; Ud Din, Israf; Arshad, Zafar; Rashid, Umer; Qazi, Umair Yaqub; Naeem, Nida (MDPI, 2022)
Syngas is a valuable entity for downstream liquid fuel production and chemical industries. The efficient production of syngas via catalytic partial oxidation of methane (CPOM) is an important process. In this study, partial oxidation of methane (POM) was carried out using CaO decorated TiO2 catalysts. The catalysts were synthesized employing the sol-gel method, while the decoration of TiO2 with CaO was achieved in an aqueous solution by wetness impregnation method. The prepared catalysts were characterized by employing XRD, Raman, TG-DTG, and SEM-EDX for structural and morphological analysis. On testing for POM, at 750 °C the catalysts demonstrate excellent CH4 conversion of 83.6 and 79.5% for 2% and 3% CaO loaded TiO2, respectively. While the average H2/CO ratio for both 2% and 3% CaO loaded TiO2, 2.25 and 2.28, respectively, remained slightly above the theoretical value (H2/CO = 2.0) of POM. The improved POM performance is attributed to the optimally loaded CaO on the TiO2 surface that promotes the reaction where TiO2 support ensure less agglomerated particles, resulting into a fine distribution of the active catalytic sites.